Characterisation and online monitoring of wear behaviour of on-machine fabricated PCD micro-tool while vertical micro-grinding of BK7 glass. (1st January 2011) - Perveen, Asma; Wong, Y.S.; Rahman, M.
This paper deals with the wear behaviour of polycrystalline diamond tool of 0.5 μm grain size during micro-grinding of BK7 glass. It was found that tool wear caused both diameter and length reduction and G ratio was found to be 940. Observation of tool surface gave clear indication of edge chipping and abrasion type of tool wear where grain was pulled out and micro-cracks and built up edge mechanism are responsible for wear mode. Tool wear progress can be divided into three stages. In the initial stage, tool suffers insignificant wear, then intermediate wear, and finally, severe worn out tool. Huge pitting on bottom surface, chipped side wall, longer centre line and double side wall lining are the major phenomena of severe tool wear. Moreover, the increasing tendency of normal cutting force is found to support the evidence of tool blunting but cannot clearly indicate the severity of wear. Monitoring of root mean square acoustic emission signal is found to give an indication of tool topographic condition, i.e., sharpness and bluntness of cutting edge. Moreover, this signal can also envisage minor and major tool chipping condition. Hence, monitoring the AE signal can be a plausible way of monitoring PCD tool condition.